SURABAYA ADOLESCENT'S PERCEPTION OF WOMEN'S SENSUALITY IN THE SHOWING “SHOWING IN THE SWIMMING POOL!! BILYY CAN’T STAND” - YOUTUBE CRAZY NIKMIR REAL - Syarizal Agam Mahendra; Heidy Arviani (JOSAR (Journal of Students Academic Research), 2021)
With so many YouTube channels and videos in Indonesia, there is competition. In addition, YouTube videos in Indonesia are also often found in the form of shows that violate the policies that have been made by Youtube. Like several video uploads on Nikita Mirzani's Youtube channel which eventually sparked controversy. One of them is titled “Buka-Bukaan di Kolam Renang!! Billy Gak Kuat” which has 15 million views and 198,000 likes and 25,000 dislikes. This video contains shows full of scenes of female sensuality. The purpose of this study was to determine the Surabaya youth's perception of female sensuality in the show "Buka-Bukaan Di Kolam Renang!! Bilyy Gak Kuat” - Youtube Crazy Nikmir Real. The research method used is descriptive qualitative by using the function of perception as a research reference. The data in this study were collected by in-depth interviews and documentation. According to the theory of perception which is divided into three stages, namely sensation, attention and interpretation, the results of this study indicate that there are differences in each individuals who are influenced by their life background, especially based on their profession, environment, personal experience, and so on experienced by the informant